Functions of peasant family farming in the municipality of Calpan, Puebla - Blanca-Bautista, Martina; Ocampo-Fletes, Ignacio; Juárez-Sánchez, José Pedro; Herrera-Cabrera, Braulio Edgar; Pérez Ramírez, Efraín; Sánchez-Morales, Primo (Revista Mexicana de Ciencias Agrícolas, 2023)
The concept of multifunctionality assumes that agriculture fulfills non-market functions, such as food, environmental, social, and cultural functions. It is a way to move towards a sustainable agriculture more respectful of human beings and the environment, which persists in different agricultural territories. However, it is pressured by economic activities for business purposes, which has generated its deterioration. The research objective was to identify the main functions of peasant family farming in the municipality of Calpan, Puebla. A survey was applied in 2020 with the aim of capturing information on the different social processes related to the multifunctionality of family farming. A stratified random sampling (SRS) with Neyman distribution was applied to determine the sample size, resulting in a sample of 81 producers. Among the main functions are: the sociocultural ones, 81% base their agricultural practices on the lunar phases; in the environmental ones is the conservation of agrobiodiversity; in the economic ones, agriculture is the primary source of income for 45%, generates jobs for 100% and contributes to food security in corn and beans for 53%. Finally, in the territorial ones, the intergenerational replacement stands out, 75% of young people who wish to continue participating in agricultural activities. It is concluded that peasant family farming is fundamental since it preserves social, cultural, economic, environmental, and territorial functions that benefit families, the environment, and society.